Infection prevention and control practice for Crimean-Congo hemorrhagic fever-A multi-center cross-sectional survey in Eurasia. - Tom E Fletcher; Abuova Gulzhan; Salih Ahmeti; Seif S Al-Abri; Zahide Asik; Aynur Atilla; Nick J Beeching; Heval Bilek; Ilkay Bozkurt; Iva Christova; Fazilet Duygu; Saban Esen; et al. (PLoS ONE)
Background Crimean Congo Hemorrhagic Fever (CCHF) is a life threatening acute viral infection that presents significant risk of nosocomial transmission to healthcare workers. Aim Evaluation of CCHF infection prevention and control (IP&C) practices in healthcare facilities that routinely manage CCHF cases in Eurasia. Methods A cross-sectional CCHF IP&C survey was designed and distributed to CCHF centers in 10 endemic Eurasian countries in 2016. Results Twenty-three responses were received from centers in Turkey, Pakistan, Russia, Georgia, Kosovo, Bulgaria, Oman, Iran, India and Kazakhstan. All units had dedicated isolation rooms for CCHF, with cohorting of confirmed cases in 15/23 centers and cohorting of suspect and confirmed cases in 9/23 centers. There was adequate personal protective equipment (PPE) in 22/23 facilities, with 21/23 facilities reporting routine use of PPE for CCHF patients. Adequate staffing levels to provide care reported in 14/23 locations. All centers reported having a high risk CCHFV nosocomial exposure in last five years, with 5 centers reporting more than 5 exposures. Education was provided annually in most centers (13/23), with additional training requested in PPE use (11/23), PPE donning/doffing (12/23), environmental disinfection (12/23) and waste management (14/23). Conclusions Staff and patient safety must be improved and healthcare associated CCHF exposure and transmission eliminated. Improvements are recommended in isolation capacity in healthcare facilities, use of PPE and maintenance of adequate staffing levels. We recommend further audit of IP&C practice at individual units in endemic areas, as part of national quality assurance programs.